Role of Bacillus licheniformis VS16-Derived Biosurfactant in Mediating Immune Responses in Carp Rohu and its Application to the Food Industry - Giri, Sib Sankar; Sen, Shib Sankar; Jun, Jin Woo; Sukumaran, V.; Park, Se Chang (Frontiers in Microbiology, 2017)
Multifarious applications of Bacillus licheniformis VS16-derived biosurfactant were explored. Labeo rohita fingerlings were injected intraperitoneally with 0.1 mL of phosphate-buffered saline (PBS) containing the water-soluble fraction of purified biosurfactant at 0 (control), 55 (S55), 110 (S110), 220 (S220), or 330 (S330) µg mL-1 concentrations. Various immunological parameters and the expression of immune-related genes were measured at 7, 14, and 21 d post-administration (dpa). At 21 dpa, fish were challenged with Aeromonas hydrophila and mortality was recorded for 14 d. Immune parameters including such as lysozyme levels (39.29±2.14 U mL−1), alternative complement pathway (61.21±2.38 U mL−1) and phagocytic activities (33.37±1.2 %) were maximum (P < 0.05) in S220 group at 14 dpa; but immunoglobulin level (11.07±0.83 mg mL-1) was highest in S220 group at 7 dpa than in controls. Activities of digestive enzymes (amylase, protease, and lipase) were significantly higher in S220 and S330 groups, than in control. Of the cytokine gene expressions, pro-inflammatory cytokines (TNF-α and IL-1β) were down-regulated (P < 0.05) in S220 and S330 groups. Expressions of anti-inflammatory cytokines (IL-10 and TGF-β) and IKB-α were up-regulated in S220 and S330 groups at 14 dpa, with highest in S220 group. The expression of NF-κB p65 and IKK-β were down-regulated in treatment groups, with lowest (P < 0.05) in S220 group. Fish in the S220 group exhibited the highest post-challenge survival rate (72.7%). Further, biosurfactant was effective in inhibiting biofilm formation upto 54.71±1.27%. Moreover, biosurfactant efficiently removed cadmium (Cd) from tested vegetables such as carrot, radish, ginger and potato, with highest removal percentage (60.98±1.29%) was recorded in ginger contaminated with Cd. Collectively, these results suggest that isolated biosurfactant could be used in the aquaculture industry in addition to its potential for application to the food industry.